FDI In India : Determinents Of Entry Modes In India - Jain, Gaurav (2003)
Although cultural distance between countries have gained a lot of attention in the FDI literature but impact on cultural distance on entry mode has recently been extensively researched, after Kogut and Singh introduced the simple measure to calculate cultural distance between the countries. This dissertation tests the proposition that do cultural distance, Sector, or Nationality affect the entry mode strategies of multinational firms when they enter foreign countries. I focus my study by concentrating on two modes of entry; joint venture and wholly owned subsidiary. I pooled entries into India made by firms from twenty four countries (Asian and non Asian) for the period 2000-2002. Culture distance between the countries was measured on index developed by Kogut and Singh (Sum of Squares). Concentrating on three independent variables I found out that cultural distance between the home base of the investor and the target country does not exert influence on the mode of entry of multinational firms. Sector was a very influential determinant in deciding the entry mode strategy adopted by multinational firms, especially in the IT and the Finance sector. Finally, the notion that non Asian firms tend to select wholly owned subsidiaries as a mode of entry when entering a foreign country was seen evident on basis of this data but the tendency of Asian firms to select the joint venture was not palpable.